Corporate Governance: Decades of Dialogue and Data - Daily, Catherine M.; Dalton, Dan R.; Cannella, Albert A. (Academy of Management Review, 2003)
The field of corporate governance is at a crossroads. Our knowledge of what we know about the efficacy of corporate governance mechanisms is rivaled by what we do not know. This special topic forum is dedicated to continuing the rich tradition of research in this area, with the hope that the models and theories offered will propel corporate governance research to the next level, enhancing our understanding of those governance structures and mechanisms that best serve organizational functioning.